Impact of the Organizational Culture on Creative Behavior: A Field Study on a Sample of Commercial Banks Operating in Jordan - Shehadeh, Hazem Khaled (European Scientific Journal, ESJ, 2016)
This study aims to analyze the impact of the organizational culture on the creative behavior by taking a field study on a sample of commercial banks operating in Jordan. To achieve this objective, a questionnaire which included 30 items was built and developed. The reliability and the sincerity of the tool were tested. Then, the questionnaire used on a sample study of 250 employees in the commercial banks operating in Jordan was selected at random. This was done using a stratified random sample method. A number of findings found in this study include the following: a. Rise in the means of the organizational culture dimensions which include work teams, ability to adapt, and the ability to innovate. It also includes the creative behavior dimensions such as problem solving, change susceptibility, and amplitude to contact. These results indicate that the employee’s responses in the commercial banks operating in Jordan about the mentioned dimensions were positive. Also, this means that the evaluation level of these dimensions was high from their perspective. b. Existence of a statistically significant impact at the significance level (α = 0.05), for the organizational culture dimensions which are work teams, ability to adapt, and ability to innovate, and on the creative behavior of the employees at the commercial banks operating in Jordan. The study, however, gave a number of conclusions and recommendations.